2017
DOI: 10.2174/1566524017666170619113435
|View full text |Cite
|
Sign up to set email alerts
|

Proteotoxic Stress Desensitizes TGF-beta Signaling Through Receptor Downregulation in Retinal Pigment Epithelial Cells

Abstract: Background: Proteotoxic stress and transforming growth factor (TGFβ)-induced epithelial-mesenchymal transition (EMT) are two main contributors of intraocular fibrotic disorders, including proliferative vitreoretinopathy (PVR) and proliferative diabetic retinopathy (PDR). However, how these two factors communicate with each other is not well-characterized.Objective: The aim was to investigate the regulatory role of proteotoxic stress on TGFβ signaling in retinal pigment epithelium.Methods: ARPE-19 cells and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Different types of stress, like proteotoxic stress, or high glucose produce EMT in RPE cells [71,72]. In our work, we tested different pathways involved in this process that modulate expression of proteins that are vital to this process, like Akt/mTOR, and the Wnt canonical pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of stress, like proteotoxic stress, or high glucose produce EMT in RPE cells [71,72]. In our work, we tested different pathways involved in this process that modulate expression of proteins that are vital to this process, like Akt/mTOR, and the Wnt canonical pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ERK MAPK pathway plays a role in TGF-β-induced EMT and cooperates with other signaling pathways in the regulation of EMT in RPE cells. Recent studies ( Chen et al, 2014b ; Tan et al, 2017 ; Xiao et al, 2014 ) have shown that blocking the ERK1/2 pathway inhibits the phosphorylation of SMAD2 and the Jagged/Notch pathway. Inhibition of the Jagged/Notch signaling pathway can alleviate TGF-β2-induced EMT by regulating the expression of Snail, Slug and Zeb1 ( Fig.…”
Section: Survey Methodologymentioning
confidence: 99%
“…CEP135 interacts with SMAD family member 9 (SMAD9), which is involved in transforming growth factor-β (TGF-β) signaling. During the development of proliferative diabetic retinopathy, TGF-β is significantly upregulated in the aqueous humor and vitreous body [19]. SNP rs4865047 is also 50.5 kb downstream of the exocyst complex component 1 gene, EXOC1 , and the exocyst complex is required for the insulin-stimulated transport of the glucose transporter type 4 (Glut4) to the plasma membrane [14].…”
Section: Discussionmentioning
confidence: 99%